EFEK MEDIASI SENSE OF CONTROL PADA PENGARUH SMARTPHONE ADDICTION TERHADAP ACADEMIC PROCRASTINATION (Studi Pada Siswa SMK Jurusan Akuntansi Pasundan 1 Cianjur) - Dikdik Japar Sidik; Kurjono Kurjono; Meta Arief; Budi Santoso (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2022)
The purpose of this study was to obtain information about the mediating effect of sense of control on the influence of smartphone addiction on academic procrastination in students of SMK Pasundan 1 Cianjur majoring in accounting. The theory that underlies this research is the theory of gestalk cognitive psychology. This study uses a quantitative approach with a survey method and the instrument used is a questionnaire distributed to students of SMK Pasundan 1 Cianjur majoring in accounting with random sampling technique, and the sample collected is 123 respondents. The data analysis technique used an associative approach with a statistical measuring tool for path coefficients (parh analysis). Based on the results of research conducted on students of SMK Pasundan 1 Cianjur majoring in accounting, the results showed that smartphone addiction had no negative effect on sense of control, sense of control had a negative effect on academic procrastination, and smartphone addiction had a positive effect on academic procrastination. Smartphone addiction does not significantly affect academic procrastination through sense of control. The advice given in this study is on the smartphone addiction variable, students should reduce positive anticipation as the most dominating indicator. On the variable sense of control students must increase the ability to control attention as the lowest indicator, in addition to the academic variable procrastination students must reduce the level of personal initiative as the most dominating indicator